Sung versus verbal directives with young adults diagnosed with autism - Koszczuk, Katrina Marie, author; LaGasse, Ashley Blythe, advisor; Davis, William, committee member; Kees, Nathalie, committee member (Colorado State University. Libraries, 2013)
Autism Spectrum Disorder is a Pervasive Developmental Disorder characterized by deficits in three main areas: social interaction, communication, and an intense resistance to change which could include repetitive, self-stimulatory behaviors according to the American Psychiatric Association (2000). The National Institutes of Health and the U.S. Department of Health and Human Services (2012) defines a receptive language disorder as exhibited by an inability to understand the words of others, difficulties enacting verbal directives, and deficits in thought organization. These deficits can cause individuals to have difficulties while participating in school, home, and social situations, and may lead to problem behaviors. The U.S. Department of Health and Human Services (2012) has linked receptive language disorders with other disabilities including Autism Spectrum Disorder (Hoch, 2012). Because this is a largely unexplored area, research is needed to find and support therapeutic techniques addressing deficits in receptive language. Three young adult males between the ages of 14 and 22 with a primary diagnosis of Autism Spectrum Disorder were recruited by flyer and word-of-mouth from Northern Colorado. This study employed a multiple baseline across participants with repeated measures design. There were a total of 6 experimental observations with each research subject. Behavioral coding was utilized to determine if there were any mean time differences between the sung and verbal directive conditions. Because data was coded separately by the researcher and research assistant, Pearson's r was used to test inter-rater correlation through Statistical Package for Social Sciences (SPSS) software (IBM Corporation, 2012). Pearson's r = + 0.997 signifying a positive correlation between the two coders. A Repeated Measures of Analysis of Variance was applied using SAS software to test for statistical significance between the verbal and sung conditions (SAS Institute Inc., 2011). The RM ANOVA yielded no statistically significant results. However the p value of the statistic, p = 0.0769, was very close to the p value set for the present study, p < 0.05. A power analysis revealed that if an average of 10.2 seconds with a standard deviation of 6.8 seconds remained constant after recruiting a total of 7 volunteer participants, then statistical significance could be reached. Even though statistical significance was not reached, trends in the data were discussed. Overall there was a decrease in time between the verbal and sung conditions for each participant. However, this trend was not clear and variability was seen among the participants throughout the sung observations after separating and plotting the data on bar and line graphs. Future researchers should increase the sample size and eliminate inherent study design flaws to thoroughly test if there is a difference between the verbal and sung directives.
Keywords: autism; music; music therapy; singing; sung directions; sung directives